Combination of KIT and FLT3‐ITD mutation status with minimal residual disease levels guides treatment strategy for adult patients with inv(16) acute myeloid leukemia in first complete remission. Issue 4 (15th May 2022) - Wang, Jun; Dao, Feng‐Ting; Wang, Yu; Jiang, Hao; Xu, Lan‐Ping; Zhao, Xiao‐Su; Zhang, Xiao‐Hui; Liu, Kai‐Yan; Huang, Xiao‐Jun; Jiang, Qian; Qin, Ya‐Zhen
Abstract: Although several studies have investigated the benefits of allogeneic hematopoietic stem cell transplantation (allo‐HSCT) for patients with inv (16) acute myeloid leukemia (AML) in first complete remission (CR1) individually stratified by KIT or FMS‐like tyrosine kinase 3‐internal tandem duplication ( FLT3‐ ITD) mutation status or minimal residual disease (MRD) levels, evaluation based on the combination of mutation status and MRD levels remains absent. This study included 157 adult patients with inv (16) AML who were consecutively diagnosed and receiving treatment at our center. A total of 50 (31.6%) patients had KIT mutations ( KIT MU ), and the risk of relapse was significantly higher in patients with KIT MU than in patients with KIT WT ( p < 0.001). A total of 12 patients (7.6%) had FLT3 ‐ITD, and FLT3 ‐ITD + tended to be related to a higher risk of relapse ( p = 0.14). KIT MU, FLT3 ‐ITD and MRD3‐H (beta subunit of core binding factor–myosin heavy chain 11 levels >0.2% after course 2 of consolidation therapy) were independent adverse prognostic factors for relapse with patients who received allo‐HSCT at CR1 were censored at the time of transplantation. After combination, patients were categorized into molecularly defined high‐risk (M‐HR; KIT MU or FLT3 ‐ITD + with MRD3‐H; n = 30), low‐risk (M‐LR; KIT WT and FLT3 ‐ITD ‐ with MRD3‐L; n = 45) and intermediate‐risk (M‐IR; others; n = 70) groups. For the M‐HR group, allo‐HSCT significantly improved both cumulative incidence of relapse cumulative incidence of relapse (CIR) and overall survival (OS) (11.1% vs. 92.6%, p < 0.001; 90.0% vs. 34.1%, p = 0.019). For the M‐IR group, allo‐HSCT significantly improved CIR but did not affect OS (14.1% vs. 62.2%, p = 0.0004; 73.3% vs. 68.3%, p = 0.43). For the M‐LR group, allo‐HSCT had no significant effect on both CIR and OS (0% vs. 35.1%, p = 0.31; 100% vs. 78.8%, p = 0.22). Therefore, the combination of KIT and FLT3 ‐ITD mutation status with MRD levels may identify inv (16) AML patients with high‐risk who can benefit from allo‐HSCT in CR1.